Burnout and stress measurement in police officers: Literature review and a study with the operational police stress questionnaire - Queirós, Cristina (2020)
Research has demonstrated that policing is a stressful occupation and that this stresshas a negative impact on police officers’ mental and physical health, performance, andinteractions with citizens. Mental health at the workplace has become a concern dueto the costs of depression, anxiety, burnout, and even suicide, which is high amongpolice officers. To ameliorate occupational health, it is therefore crucial to identify stressand burnout levels on a regular basis. However, the instruments frequently used tomeasure stress have not valorized the specificity of policing tasks. This study aims to: (i)conduct a literature review to identify questionnaires used to assess occupational stressand burnout among police officers; (ii) analyze the psychometric characteristics of aPortuguese version of Operational Police Stress Questionnaire (PSQ-Op); and, usingthe PSQ-Op and other questionnaires, (iii) to identify operational stress, burnout, anddistress levels among Portuguese police officers. The literature review identified 108studies which use a multiplicity of questionnaires to measure burnout or occupationalstress among police officers, but few studies use specific police stress questionnaires.Sample sizes were mostly below 500 participants and studies were mainly developedin the last decade in the USA and Brazil, but also in another 24 countries, showing theextent of the interest in this topic. This study applied to 2057 police officers from theNational Portuguese Police, a force policing urban centers, and used the PSQ-Op, aswell the Spanish Burnout Inventory and the Kessler Psychological Distress Scale. Theresults show that the psychometric properties of the Portuguese version of PSQ-Op areadequate. Factorial analysis revealed two dimensions defined as social and work issues,which were associated with measures of distress and burnout. Fit indices suggested asecond-order solution called operational police stress. Overall, and considering the scalerange of each questionnaire, the results showed moderate values of operational stress,distress, and burnout. However, considering their cut-off points, 85% of the samplepresented high operational stress levels, 11% critical values for burnout, and 28% highdistress levels, with 55% of the sample at risk of a psychological disorder. These resultsreinforce the need to prevent stress and to invest in police officers’ occupational health.